FEATURES OF IMPLEMENTATION OF MUSEUM PEDAGOGY IN THE MODERN INNOVATIVE EDUCATIONAL SPACE OF UKRAINE (ON THE EXAMPLE OF MUSEUMS OF KOLOMYIA) - Korolko, Andrii; Prokopiv, Liubov; Krecko, Viktoria (Mountain School of Ukrainian Carpaty, 2020)
The article presents the results of the study aimed at identifying the features and basic approaches to the introduction of museum pedagogy on the example of museums in Kolomyia. Using the competency-based approach, the authors specify the main approaches to the formation of museum pedagogy as an effective tool for preserving the Ukrainian material and spiritual heritage, including entrepreneurship. The study identified the effective aspects of the introduction of museum pedagogy in the Carpathian educational space based on awareness and cooperation that reflect the multifunctionality of all structures of influence and ensure the effectiveness of the educational space in general. The study used theoretical methods, focused interviews as well as methods of pedagogical reconstruction, assessment of strengths and weaknesses of the work. Museum pedagogy promotes the implementation of patriotic, aesthetic, legal and moral education, which are provided by the Concept of the New Ukrainian School. The obtained results of the research confirmed the effectiveness of the chosen ways of introduction of museum pedagogy in the Carpathian educational space. This allowed to significantly increase the levels of its manifestation, namely to replace traditional learning with individual, to use innovative and non-traditional learning technologies; implement competency-based, differentiated, personality-oriented, individual approaches, innovative learning technologies; plan subject-to-subject ways to get feedback; to promote universal human values.